Pengaruh Literasi Digital Dan Kepercayaan Diri Terhadap Kesiapan Kerja Generasi Z Di Kota Tasikmalaya - Nuri Nurlita; Herdiyanti Herdiyanti (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This research aims to determine the influence of digital literacy and self-confidence on Generation Z's work readiness in Tasikmalaya City. This research uses a quantitative approach with an associative type of research. The research population was Generation Z aged 20–24 years in Tasikmalaya City with a sample size of 100 respondents determined using the Slovin formula and purposive sampling technique. Data was collected through distributing questionnaires with a Likert scale that measured the variables of digital literacy, self-confidence and work readiness. The data analysis technique uses multiple linear regression with the help of statistical software (SPSS). The research results show that digital literacy has a positive and significant effect on work readiness. This shows that the ability to utilize digital technology, manage information, communicate and solve digital-based problems can increase individual readiness in facing the world of work. Apart from that, self-confidence also has a positive and significant effect on work readiness.